If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 48 + -2x = 16x + 24 Reorder the terms: 48 + -2x = 24 + 16x Solving 48 + -2x = 24 + 16x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-16x' to each side of the equation. 48 + -2x + -16x = 24 + 16x + -16x Combine like terms: -2x + -16x = -18x 48 + -18x = 24 + 16x + -16x Combine like terms: 16x + -16x = 0 48 + -18x = 24 + 0 48 + -18x = 24 Add '-48' to each side of the equation. 48 + -48 + -18x = 24 + -48 Combine like terms: 48 + -48 = 0 0 + -18x = 24 + -48 -18x = 24 + -48 Combine like terms: 24 + -48 = -24 -18x = -24 Divide each side by '-18'. x = 1.333333333 Simplifying x = 1.333333333
| F-2=3f+6 | | 5(x+3)+3(x-1)=-9 | | X/4+7=14 | | 21=(5x/6)+(3x/2) | | 2(x-4)+3(x+5)=2x | | 5.3q-1.9-4.6q=-0.3q-1.5 | | 2x-8+3x+18=2x | | 33/25*10/117*27/22 | | -2y+5x=-9 | | 62-9x=7x+18 | | x/3-26 | | 2x-5=57 | | x/2=48 | | x/4+x/3=7/4 | | 2f-7=43 | | x/6=15 | | x/2=46 | | 5c-11=19 | | 4x+14=112-10x | | 4x^2+3x-7=2x-2 | | 9-5p= | | 3b+7=52 | | 10r-12=-28 | | f=(g-h+k)/5 | | y=-2/2+2 | | F(x)=4x^2-x-3 | | 22x-18=36+16x | | 2m+15=-23 | | -3y-5=-2 | | 8(x+6)+5=8x+5 | | x-7.1=5.4 | | 4x-9=6-13 |